Laura Méndez Cuenca, Poesía, compilación, estudio preliminar y edición de Ángel José Fernández. Universidad Veracruzana, Xalapa, 2024; 728 pp. - Ruiz, Mayko Osiris (El Colegio de México, 2026)
Es una reseña